Sedimentary and thermal evolution of the Eocene‐Oligocene mudrocks from the southwestern Thrace Basin (NE Greece). (2nd February 2015) - Perri, F.; Caracciolo, L.; Cavalcante, F.; Corrado, S.; Critelli, S.; Muto, F.; Dominici, R.
Abstract: Paleothermal indicators based on clay mineral and organic matter analyses, were integrated with mudrock geochemistry and stratigraphic data to define the sedimentary evolution of the southwestern Thrace Basin during the Eocene to Oligocene. This multi‐method approach allowed us to reconstruct the burial evolution of the basin in Eocene and Oligocene times and to study the mudrock composition and relate this to their provenance and source area weathering. The studied mudrocks show similar chemical variations. The distribution of some major and trace elements for the studied samples reflect heterogeneous source areas containing both felsic to mafic rocks. In particular, the Light Rare Earth Elements/Transition elements (LREEs/TEs) ratios are very high for the Avdira and Organi samples (on the average between 1.5 and 2.2 for (La + Ce)/Cr and 3.5–8 for (La + Ce)/Ni), suggesting a felsic source(s), and very low for the Samothraki, Limnos, Paterma and Iasmos samples (on the average between 0.4 and 0.6 for (La + Ce)/Cr and 0.6–1 for (La + Ce)/Ni), suggesting a mainly basic source(s). The mineralogical composition coupled with the A‐CN‐K and A‐N‐K plots suggest a complex evolution. The clay mineral data (illite percentage in I/S and the stacking order R and the Kübler Index) coupled to vitrinite reflectance analysis indicate a high to intermediate diagenetic grade for the Middle to Upper Eocene samples (from Iasmos, Gratini, Organi, Paterma, Esimi and Samotraki sections) and a low diagenetic grade for the Upper Eocene to Oligocene samples (from Limnos and Avdira sections). These data helped in interpreting the geodynamic evolution of the studied basins where the magmatic activity plays an important role. In particular, Middle to Upper Eocene sediments show high to intermediate diagenetic grade since they are located in a portion of the basin dominated by Eocene to Oligocene magmatic activity and intrusion of granitoids, whereas, the Upper Eocene to Oligocene sediments are not involved in important magmatic activity and intrusion of granitoids and, thus, show low diagenetic grade. Furthermore, Middle to Upper Eocene sediments experienced deeper burial processes caused by lithostatic load, rather than the uppermost Eocene and Oligocene sediments, in relation of their position along the stratigraphic succession. These data suggest a burial depth of at least 3–4 km with a tectonic exhumation mainly related to the extensional phases of the Miocene age.